Tax Collection Challenges and Strategic Approaches to Enhancing Taxpayer Awareness - Ariska Setiana; Imahda Khori Furqon (Inovasi Analisis Data, 2025)
Purpose – This paper aims to reconceptualise the general state of tax collection dilemmas. It also aims to reconceptualise taxpayers' consciousness. It does this by understanding how and why current compliance measures often fail in the long run. The study looks at how administrative efficiency and taxpayer compliance are connected. Design/methodology/approach – Contemporary research on tax compliance and taxpayer knowledge is characterised and synthesised through a qualitative systematic literature review with thematic content analysis. Findings – The analysis reveals that the challenges associated with tax collection stem from more than just technical aspects. They are also influenced by factors such as fairness, trust, and the quality of governance. Taxpayer awareness is a multidimensional feature driven by behavioural and social dynamics in addition to information. The findings indicate that certain policy measures, such as isolated prevention, education or reforms, may only achieve limited and short-term effectiveness. When designed alongside administrative design, behavioural insights and institutional legitimacy, compliance is more robust. Originality/value – The paper originality lies in its development of a multidimensional concept, integrating administrative, behavioural and institutional perspectives. The research combines existing theories of compliance with recent empirical discoveries. It does this in order to describe durable contradictions in earlier tax research. It also raises issues with one-sided solutions to tax reform. Research Implications – The framework is intended to serve as a platform for empirical studies. It is also intended to support putative practices. These practices focus on legitimacy, engagement, and enduring compliance.